ROLE OF ORGANIZATION CITIZENSHIP BEHAVIOR MEDIATION IN WORK MOTIVATION RELATIONSHIP TO EMPLOYEE PERFORMANCE: EMPIRICAL STUDY - Muzakki, Muzakki; Hutabarat, Hakyesga Gandauli Lungun Marito Br (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2022)
This study aims to explore the effect of work motivation on organization citizenship behavior (OCB) and employee performance and the mediating role of organization citizenship behavior (OCB) on the relationship of work motivation and employee performance. The research method used is quantitative with a total sample of 83 respondents. The findings of this study reveal that work motivation has a positive and significant effect on organization citizenship behavior, organization citizenship behavior has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, and organization citizenship behavior can mediate positively and significantly on motivational relationship work and employee performance.